Show, don't tell Education and historical representations on stage and screen in Germany and the USA - Zumhof, Tim; Johnson, Nicholas K. (Studien zur Deutsch-Amerikanischen Bildungsgeschichte / Studies in German-American Educational History, 2020)
Demonstrating, representing, or showing is at the heart of every educational action. Historical representations on screen and stage do not "teach" us history but rather influence our ideas and interpretations of it. The contributions to this volume explore the depiction of history in theater and film from the intersection of historical scholarship, aesthetics, memory studies, and education. They examine the creation of historical images, film production and reception, the scriptwriting process, educational programming, and depictions of German-American encounters. Above all else, they explore how various theatrical and filmic productions show history rather than tell it. (DIPF/Orig.)